A Comparative Study to evaluate Gingival Depigmentation using Scalpel Blade Technique and CO2 Lasers - Senthilnathan, S; Baskaran, M; Thirumalai, S; Naarayanen, MB (Journal of Orofacial Research, 2014)
Gingival pigmentation is the change in color of the oral mucosa or gingiva which can occur as a result of different lesions and conditions. Clinically melanin pigmentation is not a disease and does not have any symptoms, but only act as a major esthetic concern for people. Most of the oral pigmentation is physiologic and caused by melanin deposition. It can be treated by scalpel surgery, chemical agents (Phenol 90%), gingival abrasion, free gingival grafts, electrosurgery, cryosurgery and lasers. The treatment should be less expensive, easily available, and easy to use with minimum discomfort and pain. It should be effective for a longer time. The present study compares two effective surgical gingival depigmentation techniques — scalpel blade surgery and CO2 laser surgery.